The Implementation of the Discovery Learning Model Using Higher Order Thinking Skills Booklet Media on Students' Critical Thinking Ability - Nurhikma Ramadhana; Nur Qamariah; Hanandita Veda Saphira (IJORER : International Journal of Recent Educational Research, 2025)
Objectives: To implement and design learning models that incorporate appropriate instructional media, fostering critical thinking. Such an approach will facilitate the integration of three cognitive domains: knowing, applying, and reasoning. Methods: This study adopts a quasi-experimental design using a "true experimental design" with a post-test-only control group. The objective is to implement the Discovery Learning model and develop a Higher-Order Thinking Skills (HOTs) booklet to enhance students' critical thinking abilities. Results: The research findings indicate that the Discovery Learning model with HOTs booklet media significantly influences students' critical thinking skills in biology learning. The critical thinking aspect with the highest score is essential clarification, effectively fostered during the problem-orientation phase. This stage involves students formulating questions based on scenarios in their worksheets. Novelty: The novelty of this study lies in its integration of Discovery Learning with a hots booklet explicitly tailored to the Indonesian secondary school context. While previous studies have emphasized the individual impact of Discovery Learning or HOTs-based instructional tools, this research uniquely combines the two to create a synergistic approach that addresses the critical thinking gaps identified in Indonesian students.